Determinan Muslim Milenial dan Generasi Z di Wilayah Jabodetabek Untuk Membayar Zakat Melalui Lembaga Zakat Formal - Oseva, Jenidar; Soleh, Mohamad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the factors influencing Millennials and Gen Z's intention to pay zakat in formal zakat institutions. The Theory of Planned Behavior is used as the theoretical framework in this study by including variables of education, income, perceived religiosity, literacy, social influence, and credibility of zakat institutions. Primary data was collected through a survey of a total of 100 Millennial and Gen Z Muslim respondents in the Jabodetabek area who pay zakat through a formal zakat institution. The analysis in this study uses a logistic regression model. This study found that the level of education and the credibility of zakat institutions have a positive and significant effect on the intention or willingness of millennials and Gen Z to pay zakat through formal zakat institutions. However, the variables of income, perceived religiosity, literacy, and social influence are insignificant in this study. The implications of these findings include that BAZNAS and zakat institutions need to implement programs to increase public knowledge and develop promotional strategies for paying zakat through zakat institutions. In terms of credibility, BAZNAS must be able to formulate clear regulations to guide zakat institutions in administering zakat professionally and credibly. In addition, managers of zakat institutions must also ensure they can manage institutions professionally and credibly implement digitization (online platform) to facilitate and accelerate muzaki access to pay zakat and get information on zakat distribution. Some limitations of this research that can still be developed in other studies are the use of a larger number of samples and the coverage of other cities in Indonesia.